Alcohol Use and Sexual Assault Among College Students: Implications for APRN Practice. (January 2019) - Sheridan, Trisha; Evans, Dian Dowling
Abstract : The Research to Practice column is designed to provide advanced practice nurses (APRNs) with an analysis of a current research topic with implications for practice change within emergency care settings. This review examines a recent study conducted byTadros, Sharon, Hoffman, and Davidov (2018), titled "Emergency Department Visits for Sexual Assault by Emerging Adults: Is Alcohol a Factor?" The authors conducted a retrospective chart review of emergency department (ED) visits for sexual assault among a college-age population and found most patients were female (98%) and 70% were younger than 21 years. Additionaly, among those younger than 21 years, 74% reported alcohol use at the time of their assault and 62.3% delayed presenting to the ED for care for 24 hr or more. These and other associated findings have implications for APRN practice, including reporting and documentation of these events, and risk reduction educational strategies.